PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA KELAS V SEKOLAH DASAR - Ardiyanti, Tri; Rahayu, Theresia Sri; ,, Wasitohadi (Jurnal Karya Pendidikan Matematika, 2019)
This classroom action research aims to improve the learning outcomes of Mathematics in fifth grade students of Cebongan 03 Elementary School through the three-dimensional model of Discovery Learning. This research was conducted in two cycles through the stages of planning, implementation, observation, and reflection. Data collection is done using observation sheets for the learning process and test questions for learning outcomes. Data analysis was carried out with comparative descriptive analysis, namely comparing student learning outcomes in the pre cycle, cycle I and cycle II. From this study the following results were obtained; in the pre-cycle of 21 students only 6 students (28.57%) were completed and 15 students (71.43%) did not complete with an average grade of 51.71. Furthermore, in the first cycle, after taking action by applying the Discovery Learning learning model, a number of 9 students (42.85%) were declared complete and 12 students (57.15%) were not completed with a class average of 63.80. Then in the second cycle results were obtained that a number of 19 students (90.5%) were declared complete and 2 students (9.5%) were not completed with a class average of 85.95. This shows that the Discovery Learning learning model assisted by the media is able to improve student Mathematics learning outcomes.